2015
DOI: 10.1002/adv.21503
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Low Polymerization Shrinkage and Bis‐GMA‐Free Dental Resin System

Abstract: ABSTRACT:Because of the estrogenic effect of bisphenol A (BPA), the application of BPA derivatives such as Bis-GMA in dentistry has been doubted. In this research, Bis-GMA-free dental resin systems were prepared by mixing 1,6-bis(2 -methacryloyoxy-ethoxycarbonyl-amino)-2,4,4-trimethylhexane (UDMA), silicon containing dimethacrylate monomer (SiMA), and triethyleneglycol dimethacrylate (TEGDMA) together with different mass fraction. Double bond conversion, polymerization shrinkage, flexural strength, flexural, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Usually, they are powdered and then mixed, in small amounts, with a dry potassium bromide (KBr) powder [18,29,45,59,90,92,[98][99][100][101][102]. In recent works attenuated total reflection (ATR) sampling technique was effectively used for the DC determination [85,91,[103][104][105][106][107][108]. The main advantage of the ATR-FTIR is simplicity in sample processing.…”
Section: Fourier Transformed Infrared (Ftir) Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, they are powdered and then mixed, in small amounts, with a dry potassium bromide (KBr) powder [18,29,45,59,90,92,[98][99][100][101][102]. In recent works attenuated total reflection (ATR) sampling technique was effectively used for the DC determination [85,91,[103][104][105][106][107][108]. The main advantage of the ATR-FTIR is simplicity in sample processing.…”
Section: Fourier Transformed Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…The dimethacrylate group provides bands in the FTIR spectra at 1637 cm −1 , referring to the C=C stretching vibrations [18,29,54,85,[90][91][92][98][99][100][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], 948 cm −1 -referring to the =CH 2 wagging and 816 cm −1 -referring to the =CH 2 twisting [112]. Since the peak at 1637 cm −1 is stronger [112], it is most commonly used.…”
Section: Fourier Transformed Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…Water Sorption and Solubility. Low interaction of dental composites with water is highly desirable to maintain physical/mechanical properties, 62 increase the chemical stability, 63 and minimize leaching of the low-molecular-weight species into the oral environment. Different procedures have been employed to evaluate the water sorption (WS) and water solubility (WSl) of dental composite materials and their resin matrix.…”
Section: Preparation Of Dental Composites Andmentioning
confidence: 99%
“…In addition, several researches showed that mechanical properties could be improved by introducing fluorine into a dental monomer [24,25,26]. All of these properties make fluorinated polymers very attractive for dental application.…”
Section: Introductionmentioning
confidence: 99%